Landscapes of support for farming mental health: Adaptability in the face of crisis. (8th December 2022) - Shortland, Faye; Hall, Jilly; Hurley, Paul; Little, Ruth; Nye, Caroline; Lobley, Matt; Rose, David Christian
Abstract: Poor mental health is an important and increasingly prevalent issue facing the farming industry. The adaptability of what we, in this article, describe as 'landscapes of support' for farming mental health is important to allow support systems to adapt successfully in times of crisis. The term 'landscapes of support' refers to the range of support sources available to farmers, including government, third sector bodies and farming/community groups. This article seeks to understand the factors influencing the adaptability of these landscapes of support, especially at a time of crisis. Using a case study of the UK, we undertook a literature review, interviews with 22 mental health support providers and an online survey of people within landscapes of support (93) and farmers themselves (207). We also held an end‐of‐project workshop. Using an adapted three‐point framework to assess adaptability, we found that support‐giving organisations adapted during the pandemic using a range of interventions (e.g., enhanced digital offering, use of media), but implementation was affected by organisational challenges (e.g., limited digital training, funding shortfalls, staff trauma) and operational constraints (e.g., lack of capacity, rural digital divide, tension between providers, stigma). We discuss how landscapes of support for farming mental health can be made more sustainable to deal with future shocks.